The Existence of the Quarter Life Crisis Phenomenon in Young Adults on Post-Covid-19 Mental Health in Parepare City Communities - M. Nasir; Muhammad Wajdi; Abidin Abidin; Edi Hasan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to explore the phenomenon of Quarter Life Crisis among young adults in Parepare City before and after the Covid-19 pandemic and its impact on mental health. This ex-post facto research involved young adults without permanent jobs in Parepare City. A purposive sampling technique was employed, with a total sample of 300 respondents. The study results indicate a significant effect of Quarter Life Crisis on Covid-19 prevention (Sig. 0.002 < 0.005) and on mental health (Sig. 0.014 < 0.05). A mental health workshop is proposed as an intervention to assist individuals experiencing a Quarter Life Crisis.